Extracellular LGALS3BP regulates neural progenitor position and relates to human cortical complexity - Christina Kyrousi (Nature Portfolio, 2021)
Basal progenitors are enriched in gyrencephalic species like humans contributing to neuronal expansion. Here the authors show that LGALS3BP de novo variants are related to reduced cortical complexity and area in humans and that LGALS3BP regulates neural progenitor position in organoids, human fetal tissue and mice.